Analisis Statistik Chi-Square Terhadap Efektivitas Suplemen Tablet Zat Besi dalam Meningkatkan Kadar Hemoglobin - Dian Mustofani; Hariyani Hariyani; Rahmawati Erma Standsyah (Mathematics Department, Faculty of Sciences and Technology Unisda Lamongan, 2025)
This study aims to evaluate the impact of consuming iron supplementation tablets (TTD) along with milk on hemoglobin levels among adolescent girls, using the Chi-Square statistical analysis approach. A quasi-experimental design with a pretest-posttest control group was applied. The subjects consisted of 58 respondents, divided into two groups: intervention (TTD + milk) and control (TTD only). Hemoglobin levels were measured before and after the intervention and categorized as